The relationship between professional autonomy and moral distress among nurses working in children's units and pediatric intensive care wards - Sarkoohijabalbarezi, Zahra; Ghodousi, Arash; Davaridolatabadi, Elham (International journal of nursing sciences, 2017)
Nurses serve as the primary source of care for minor patients in intensive care units. Even though they support both patients and their relatives, these nurses may experience moral distress from their profession. While managing their daily relationships with their patients, nurses must also be able to control their actions to feel that they are from a social unit and feel their competence in association with others. This study aimed to investigate the relationship between professional autonomy and moral distress among nurses working in children's units and pediatric intensive care wards. This descriptive/comparative cross-sectional study was conducted in 2015 using 120 nurses as subjects. Subjects were selected using the census method. The research tools used to gain measurable data were the Pankratznursing questionnaire(PNQ) and Corley'sMoral distress scale (MDS). In order to analyze the collected data, descriptive statistic tests such as the relative frequency distribution, mean, standard deviation and the Pearson correlation test, T-test, ANOVA, and regression were used. The SPSSv.20 software was also used to analyze the data obtained. The relationship between professional autonomy and moral distress revealed that there was a significant positive relationship between professional autonomy and moral distress in the intensity (r = 0.39; P < 0.001) and the iteration (r = 0.41; P < 0.001). In addition, professional autonomy predicted 18% of changes in intensity of moral distress in total(MR = 0.42, R2 = 0.18) and also professional autonomy predicted 25% of iteration in moral distress in total(MR = 0.507, R2 = 0.25). The results of this study revealed that there was a direct positive relationship between professional autonomy and moral distress.